Comparatuve analysis of infrastruture for processing using a decision support system for the calculation of cost of phase of post-harvest coffee - Santos, Rafael Vargas; Vieira, Henrique Duarte; Borém, Flávio Meira; Isquierdo, Eder Pedroza (Coffee Science - ISSN 1984-3909, 2014)
The infrastructure sizing for processing the coffee is decisive in the profitability of coffee, and will depend on several factors. Thus, due to the existence of so many variables it is common to underestimate or overestimate producer aspects of infrastructure. The objective of this work related to the area of yard aspects of infrastructure and capacity of the dryers farms was analyzed in the post-harvest coffee. Forty-six farms in the regions of the Cerrado, Matas de Minas and southern Minas Gerais answered a questionnaire in order to enable this analysis. By employing the decision support system for calculating the cost of post harvest coffee, these farms was found to overestimate the area of the yard and correctly estimate the capacity of the dryers.